2020
DOI: 10.12669/pjms.36.6.2088
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between hormone levels and cardiovascular autonomic neuropathy in menopausal patients with diabetes mellitus

Abstract: Objective: To discuss the correlation between hormone levels and cardiovascular autonomic neuropathy (CAN) in menopausal patients with Type-2 diabetes mellitus (T2DM). Methods: This clinical research study was conducted at Department of Endocrinology, Baoding No. 1 Hospital from January 2016 to December 2017. In this study a total of 386 menopausal female patients with T2DM were selected and classified into two groups according to the CAN function test: the CAN group (80 cases) and the DM group (306 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In this study, it was found that cholesterol levels in perimenopause women with type 2 DM did not increase compared to type 2 DM in men. This agrees with Zhang's study exploring sexual dimorphism in adipose tissue accrual and deposition [7]. Explaining the mechanism by which sex hormones can modulate the modes of fat accumulation and storage due to obesity and metabolic syndrome, and the rapid increase in the predisposition to these diseases after menopause.…”
Section: Lilliefors Significance Correctionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, it was found that cholesterol levels in perimenopause women with type 2 DM did not increase compared to type 2 DM in men. This agrees with Zhang's study exploring sexual dimorphism in adipose tissue accrual and deposition [7]. Explaining the mechanism by which sex hormones can modulate the modes of fat accumulation and storage due to obesity and metabolic syndrome, and the rapid increase in the predisposition to these diseases after menopause.…”
Section: Lilliefors Significance Correctionsupporting
confidence: 90%
“…Explaining the mechanism by which sex hormones can modulate the modes of fat accumulation and storage due to obesity and metabolic syndrome, and the rapid increase in the predisposition to these diseases after menopause. The results of research on the relationship between estrogen levels and the incidence of cardiovascular disease autonomic neuropathy (CAN) in menopause women with type-2 diabetes mellitus (DMT2), obtained the results of multifactor logistic regression analysis showing HbA1c (OR=3980.95% CI=1268~ 10319) and estradiol (OR=3.075, 95%CI=1.167~7.366) is an independent risk factor for CAN, so CAN morbidity will increase in menopause female patients with type 2 DM [7].…”
Section: Lilliefors Significance Correctionmentioning
confidence: 99%
“…Most recent study from China, also depicted quite high frequency of DCAN, that is 80 out of 386 (20.72%) had DCAN in menopausal T2DM patients. 14 Age” is one of the confounding factors 15 , but in our study all subjects were age matched so age is not a confounding factor in our study. We found that mean age of Definite CAN cases was 48.67±5.6 and Severe CAN was 50.9±9.39 years, our results are supported by another related study conducted at Faisalabad, Pakistan which showed that mean age of CAN positive diabetics was 52.99±7.00 years.…”
Section: Discussionmentioning
confidence: 86%
“…Elevated glucose levels could trigger microvascular alterations and increased production of inflammatory factors, including CRP, IL-6, and TNF- α [ 131 ]. Serum hs-CRP is linked with diabetic neuropathy occurrence, one of the most prevalent diabetes complications [ 132 134 ]. Nevertheless, in male and female patients, symptomatic peripheral diabetic neuropathy and inflammation are related to endothelial dysfunction and elevated CRP serum levels [ 135 ].…”
Section: T2dm and Inflammationmentioning
confidence: 99%